Benjamin Franklin : an American life - Isaacson, Walter (New York : Simon & Schuster, 2003)
Tells the life story of founding father Benjamin Franklin, describing the many hats he wore, from inventor to businessman to statesman; the persona he created--and that still lives on; and his relationships with his wife, his illegitimate son, and his illegitimate grandson
Includes bibliographical references and index.
Keywords: Franklin, Benjamin, 1706-1790.; Statesmen -- United States -- Biography; Scientists -- United States -- Biography; Inventors -- United States -- Biography; Printers -- United States -- Biography; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1789.